Admonitio Generalis, a testimony to the influences of the Collecttio Dionisiana on Carolingian Legislation - Bardu , Rareș (BLACK SEA REGION AT THE CROSSROADS OF CIVILIZATIONS, 2026)
The canonical collection of the Proto-Romanian scholar from Scythia Minor (present-day Dobrogea), Dionysius Exiguus ("the humble"), known as the Dionisiana, represented a crucial landmark not only in the formation and consolidation of Western European Canon Law, but also in promoting the ecumenical unity of the Church during the first millennium, by codifying a shared canonical foundation for both East and West. The prestige enjoyed by this collection led to its adoption as a model and source of juridical authority by Charlemagne, in the renowned programmatic decree Admonitio Generalis of 789, which laid the groundwork for his legislative unification efforts within the Frankish Empire. Thus, through the interweaving of canonical legislation with civil law throughout the medieval period, Dionisiana exerted a decisive influence on the genesis and development of Western Christian juridical culture and its juridical institutions.